(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The aim of this research is to identify the general level of teachers’ curriculum expectations in (geography subject as a model), as well as the significance of the difference in the level of teachers’ curriculum expectations in light of the gender variables (male, female), the years of service (10 years or less - more than 10 years), the level of attitudes of fourth-grade literary students towards geography, the level of congruence between teachers’ curriculum expectations and the attitudes of fourth-grade literary students towards geography in light of the variables, the general level of congruence and the level of congruence between teachers’ curriculum expectations and the attitudes of students in the fourth literary class towards geography, the level of congruence between teachers’ curriculum expectations and the attitudes of their students in the class fourth literary towards geography, the level of congruence between the expectations of male and female teachers (with 10 years of service 10 and less), the methodology and the attitudes of female students in the fourth literary grade towards geography, the level of congruence between the expectations of male and female teachers (with more than 10 years of service), and the methodology and attitudes of female and male students in the fourth literary grade towards the subject of geography. thus, The methodological expectations tool was applied to a random sample of teachers of geography with a total of (73) participants, while the tool for students’ attitudes towards geography was applied to a random sample of fourth-grade literary middle or secondary students, totaling (872) male and female students. The results showed that there is a positive significance in the curriculum expectations of the teachers of geography for the fourth preparatory literary class, As well as there is a significance difference according to the gender variable in the level of curriculum expectations of teachers in favor of males, there is significance difference according to the variable of years of service in the level of curriculum expectations of teachers in favor of those with service more than 10 years, there is a positive significance in the attitudes of the fourth literary students towards the geography subject, there is a relative match at the level (positive extrusive graph) between the two variables (Teachers’ curriculum expectations) and (the fourth grade literary students’ attitudes towards geography), there is a relative (general) match between the two variables and with a significant difference in favor of (curriculum teachers) among the study sample, there is a relative match between the two variables with a significant difference in favor of female teachers among the female students, there is a relative match between the two variables and a significant difference in favor of the teachers over the students, there is a causal match between the two variables and a significant difference in favor of teachers with service (10 years and less) among the study sample, and there is a relative match between the two variables and a significant difference in favor of teachers with service (more than 10 years) among the study sample, according to these results appropriate relevant recommendations and suggestions were presented.